Representation for uncertainty trust of WSN based on lightweight-cloud - Xiao-bin XU; Guang-wei ZHANG; Shang-guang WANG; Qi-bo SUN; Fang-chun YANG (Tongxin xuebao)
According to the characteristic of qualitative and quantitative uncertainty conversion ability of cloud model, a lightweight cloud model was designed, and the uncertainty representation of direct trust, indirect trust, and recommenda-tion trust in WSN was proposed. The computation cost of lightweight cloud model is quite low so that a single node can build lightweight cloud model independently and evaluate the trust of other nodes to find out the safety hazards in WSN. Simulations in multiple scenarios verify the effectiveness of the proposed method. Simulation results show that this method overcomes the contradiction between the sensitivity and tolerance of traditional trust management framework, furthermore, it's not only tolerant of abnormal conditions, but also sensitive to multiple attacks.